Pengaruh Lama Perendaman Dalam Larutan Sukrosa Terhadap Karakteristik Osmodehidrat Buah Salak Pondoh (Salacca Zalacca) - Virya Raharja, Adithia; Timur Ina, Putu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i04.p12, 2022)
This research aims to determine the effect of immersion time in sucrose solution on the osmodehydrous characteristics of pondoh snake fruit and determine the duration of immersion in sucrose solution to produce osmodehydrous of pondoh snake fruit with the best characteristics. The treatment of immersion time in 60% sucrose solution used was 9 hours, 12 hours, 15 hours, 18 hours and 21 hours. This study used a completely randomized design with three repetitions to obtain 15 experimental units. The data obtained were analyzed by means of variance and if the treatment had a significant effect, it was continued with the Duncan test. The results showed that the duration of immersion in 60% sucrose solution significantly affected moisture content, water loss, dissolved solids, weight loss, antioxidant activity and total sugar. The results showed that the immersion in 60% sucrose solution with the duration time of 21 hour had the best treatment which resulted in moisturecontent 6,34%, water loss 92,55%, solid gain 69,88%, weight loss 22,89%, antioxidant activity 3,04%, total sugar 20,15%, taste liked, color liked, texture liked, flavor liked and overall acceptance liked.